The Impact of Windows Replacement on Airtightness and Energy Consumption of a Single Apartment in a Multi-Family Residential Building in Montenegro: A Case Study - Esad Tombarević; Igor Vušanović; Milan Šekularac (Energies, 2023)
One of the important factors influencing the thermal performance of buildings is the leakage of the envelope. When it comes to Montenegro, although there is a formal airtightness requirement, air permeability tests are not mandatory and therefore there is a lack of data in this regard. This paper reports the results of fan pressurization tests on a single apartment in a multi-family residential building before and after replacing the windows. The replacement of old wooden windows with new UPVC ones, provided that the installation is carefully supervised, proved to be an effective air tightening measure, as it resulted in a reduction of air change rate at the reference building pressure from 6.25 h−1 to 0.77 h−1, or by nearly 90%. The energy impact of air leakage was evaluated using the national software for calculating the energy performance of buildings based on the DIN V 18599 methodology. Calculations showed that by reducing infiltration, significant energy savings for heating can be achieved, while savings for cooling are practically negligible. Savings in relative terms were greater when the façade walls were thermally insulated and when the building was located in a colder climate zone. Savings in delivered energy ranged from 13 to 25 kWh/m2·year, depending on the climate zone.